Cessation of screening for intestinal carriage of extended-spectrum β-lactamase-producing Enterobacteriaceae in a low-endemicity intensive care unit with universal contact precautions. (April 2018) - Jalalzaï, W.; Boutrot, M.; Guinard, J.; Guigon, A.; Bret, L.; Poisson, D.-M.; Boulain, T.; Barbier, F.
Abstract: Objectives: The usefulness of screening for carriage of extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-E) with active surveillance cultures (ASC) remains equivocal in low-endemicity intensive care units (ICUs). Our primary objective was to appraise the impact of ceasing ASC on the incidence of ICU-acquired ESBL-E infections in an ICU with universal contact precautions (CP). Patient outcomes and carbapenem consumption were also investigated. Methods: A single-ICU, retrospective, uncontrolled before-and-after study including all patients admitted for ≥3 days during two consecutive 1-year periods with and without ASC. Results: A total of 524 and 545 patients were included during the ASC and the no-ASC periods, respectively. Twenty-eight patients (5.3%) from the ASC period were ESBL-E carriers. An ICU-acquired ESBL-E infection (median duration of risk exposure, 4 (range 2–9) days for both periods) occurred in 1.1% and 1.5% of patients admitted during the ASC and the no-ASC periods (p = 0.64), with no inter-period variation in incidence after adjustment on competing risks of death and ICU discharge (standardized hazard ratio (SHR) 2.32, 95% CI 0.80–6.73, p = 0.12). An admission during the no-ASC period exerted no independent impact on the hazards of ESBL-E infections (adjusted OR 1.16, 95% CI 0.38–3.50, p = 0.79), in-ICU death (SHR 1.22, 95% CI 0.93–1.59, p = 0.15) and extended length of stay (SHR for discharge 0.89, 95% CI 0.79–1.01, p = 0.08). Carbapenem exposure in patients without ESBL-E infection decreased between the ASC and no-ASC periods (75 versus 61 carbapenem-days per 1000 patient-days, p = 0.01). Conclusions: In a low-endemicity ICU with universal CP, the withdrawal of routine screening for ESBL-E carriage had no significant effect on the incidence of ICU-acquired ESBL-E infections and patient outcomes. Carbapenem consumption decreased in patients without ESBL-E infection.